Accreditation process in European countries - an EFLM survey - Boursier,G.; Vukasovic,I.; Brguljan,P.M.; Lohmander,M.; Ghita,I.; Bernabeu Andreu,F.A.; Barrett,E.; Brugnoni,D.; Kroupis, C.; Sprongl,L.; Thelen,M.H.; Vanstapel,F.; et al. (Clin.Chem.Lab Med., 2016)
BACKGROUND: Accreditation is a valuable resource for medical laboratories. The development of quality systems based on ISO 15189 has taken place in many laboratories in the European countries but data about accreditation remain scarce. The EFLM Working Group "Accreditation and ISO/CEN standards" conducted a survey that reviews the current state of the accreditation process in European countries. METHODS: An on-line questionnaire was addressed to delegates of 39 EFLM scientific societies in March 2014. One answer by country was taken into account. The survey was dealing with mandatory status, number of accredited medical laboratories in each country, possibility of flexible scope and concerned medical fields. The status of point-of-care testing (POCT) in each country was also studied. RESULTS: Twenty-nine responses (74%) were registered. All the assessed countries (100%) have begun an accreditation process in various ways. All the national accreditation bodies (NAB) offer or are working to offer an ISO 15189 accreditation. The accreditation process most often concerns all phases of the examination and various medical fields. Medical laboratories are responsible for POCT in 20 (69%) countries. The accreditation process for POCT, according to ISO 15189 and ISO 22870, is also developing. CONCLUSIONS: While there are several variations in the approaches to accreditation of medical laboratories in the European countries, the ISO 15189 accreditation project has been widely accepted. The use of a unique standard and the cooperation among countries due to scientific societies, EFLM, accreditation bodies and EA enable laboratory professionals to move toward uniform implementation of the accreditation concept
DA - 20160309 IS - 1437-4331 (Electronic) IS - 1434-6621 (Linking) LA - eng PT - Journal Article PT - Research Support, Non-U.S. Gov't SB - IM